A Comparison of Platelet Stickiness Tests during an Atromid-S Trial - O’Brien, J. R; Path, F. C; Heywood, Joan B. (Thrombosis and Haemostasis, 1966)
Seven patients were studied before and throughout 16 weeks’ treatment with Atromid-S. The typical cholesterol-lowering effect of this drug was found. The bleeding time increased considerably in 6 out of 7 patients, but platelet adhesiveness tested in a glass filter and in the Wright Rotator was not decreased.New methods recently devised for the quantitation of the platelet response to adenosine diphosphate, adrenaline, 5-hydroxytryptamine and “collagen” were used. The average response to collagen decreased slightly and that to adrenaline increased slightly during the treatment period. The response to 5-hydroxytryptamine, the collagen and the Wright tests were significantly interrelated but no other associations were found between any “stickiness” tests or between these tests and the serum cholesterol or uric acid levels. Accordingly, most test seem to measure different and in independent parameters of platelet behaviour.